Α‐Mangostin suppresses the de novo lipogenesis and enhances the chemotherapeutic response to gemcitabine in gallbladder carcinoma cells via targeting the AMPK/SREBP1 cascades. Issue 1 (25th November 2019) - Shi, Yu; Fan, Yangwei; Hu, Yuan; Jing, Jiayu; Wang, Chuying; Wu, Yinying; Geng, Qianqian; Dong, Xuyuan; Li, Enxiao; Dong, Danfeng
Abstract: High rates of de novo lipid synthesis have been discovered in certain kinds of tumours, including gallbladder cancer (GBC). Unlike several other tumours, GBC is highly insensitive to standard adjuvant therapy, which makes its treatment even more challenging. Although several potential targets and signalling pathways underlying GBC chemoresistance have been revealed, the precise mechanisms are still elusive. In this study, we found that α‐Mangostin, as a dietary xanthone, repressed the proliferation and clone formation ability, induced cell cycle arrest and the apoptosis, and suppressed de novo lipogenesis of gallbladder cancer cells. The underlying mechanisms might involve the activation of AMPK and, therefore, the suppression of SREBP1 nuclear translocation to blunt de novo lipogenesis. Furthermore, SREBP1 silencing by siRNA or α‐mangostin enhanced the sensitivity of gemcitabine in gallbladder cancer cells. In vivo studies also displayed that MA or gemcitabine administration to nude mice harbouring NOZ tumours can reduce tumour growth, and moreover, MA administration can significantly potentiate gemcitabine‐induced inhibition of tumour growth. Corroborating in vitro findings, tumours from mice treated with MA or gemcitabine alone showed decreased levels of proliferation with reduced Ki‐67 expression and elevated apoptosis confirmed by TUNEL staining, furthermore, the proliferation inhibition and apoptosis up‐regulation were obviously observed in MA combined with gemcitabine treatment group. Therefore, inhibiting de novo lipogenesis via targeting the AMPK/SREBP1 signalling by MA might provide insights into a potential strategy for sensitizing GBC cells to chemotherapy.